Water quality status in industrial area at Semenyih River, Selangor - Abd Satar, Mohd Imtiaz Shahren (2018)
River is the most important water resource for human and aquatic lives. The quality of the river has been deteriorated by human activities and this caused serious water pollution. This study was carried out to determine the Semenyih River water quality in industrial area based on the physicochemical and biological parameters. The sampling was conducted in dry season during 2017. Water samples were collected from three stations along the river. Sample was taken once a week for six weeks, beginning at the end of July until the middle of September 2017 at three stations selected. Six parameters were selected as indicators to assess water quality status based on DOE-WQI index. The parameters were in-situ analysis for dissolved oxygen (DO) and pH and ex-situ analysis for biological oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (NH3N) and total suspended solid (TSS). Results showed that the river was slightly polluted with NH3-N. Furthermore, the result pointed out that water quality deterioration in the river was associated with industrial activities. One Way Analysis of Variance (ANOVA) was used to compare the water quality index based on DOE-WQI index. The water quality index values at the study areas ranged from 47.87 to 72.09 or in Class III and IV. Therefore, the river water can be used for irrigation with precaution but extensive treatment needed before using for domestic purposes.